2012
DOI: 10.1123/jsr.21.4.306
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Peak Ground-Reaction Force During 60-cm Drop Landings Caused by a Single Session of Repeated Wingate Anaerobic Tests

Abstract: A single session of repeated conditions of anaerobic muscle fatigue induced by WATs caused an initial reduction in peak F2 force followed by an increase in peak F2 force across conditions. Muscle fatigue consequently alters landing kinetics, potentially increasing the risk of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
(77 reference statements)
1
4
0
Order By: Relevance
“…This finding would be consistent with the previously published findings of Shimokochi et al 28 ) who demonstrated a lowering in the activation of the gastrocnemius muscle and plantarflexor moment, in combination with an increase in the moment of ankle dorsiflexion, decreased plantarflexion angle at IC and decreased time-to-peak VGRF in subjects instructed to land on heel with body as upright as possible, compared to land on forefoot with forward lean of the body. Although non-significant, our identified effects of fatigue in lowering peak VGRF agree with the findings of Kernozek et al 29 ) , Weinhandl et al 30 ) , Coventry et al 27 ) , and James et al 31 ) , but not with the findings of an increase in peak VGRF with fatigue reported by Dominguese et al 19 ) and Brazen et al 32 ) . In our study, we predict that the decrease in peak VGRF was caused by fatigue of the knee extensors after the high-intensity exercise.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding would be consistent with the previously published findings of Shimokochi et al 28 ) who demonstrated a lowering in the activation of the gastrocnemius muscle and plantarflexor moment, in combination with an increase in the moment of ankle dorsiflexion, decreased plantarflexion angle at IC and decreased time-to-peak VGRF in subjects instructed to land on heel with body as upright as possible, compared to land on forefoot with forward lean of the body. Although non-significant, our identified effects of fatigue in lowering peak VGRF agree with the findings of Kernozek et al 29 ) , Weinhandl et al 30 ) , Coventry et al 27 ) , and James et al 31 ) , but not with the findings of an increase in peak VGRF with fatigue reported by Dominguese et al 19 ) and Brazen et al 32 ) . In our study, we predict that the decrease in peak VGRF was caused by fatigue of the knee extensors after the high-intensity exercise.…”
Section: Discussionsupporting
confidence: 85%
“…For the fatigue session, participants again completed a brief warm-up, followed by high-intensity interval exercise on a cycle ergometer (POWERMAX V3, KONAMI Sports & Life, Japan). The high-intensity interval exercise was designed to induce lower limb muscle fatigue in a short period of time 18 , 19 , 20 , 21 ) . The exercise consisted of six, 30 s, bouts of maximum velocity pedaling, repeated at 5-min intervals.…”
Section: Methodsmentioning
confidence: 99%
“…The IEP used in the current study differed from the majority of previous exercise protocols that have investigated changes in landing mechanics. 3 , 5 , 8 , 11 , 17 , 18 , 22 , 24 , 28 , 42 Our goal was to elicit individualized submaximal fatigue congruous with most sporting situations. Participants perceived the work to be “hard” on the “ratings of perceived exertion” scale; these values are consistent with those of young, elite soccer players following matches and training sessions (14.4 ± 1.2).…”
Section: Discussionmentioning
confidence: 99%
“…The only changes relative to the start of the IEP during the 90 minutes of exercise were decreases in hip loading and hip flexion at initial contact (factor 2) and plantar flexor loading and knee shear force (factor 6), both of which did not occur until the end of the IEP. Previous studies demonstrating changes in double-leg landing biomechanics have used Wingate tests, 8 repetitive squatting, 18 shuttle exercise including 30-meter sprints and alternating vertical jumps, 3 vertical jumping, 11 , 17 step and bounding drills, 22 and treadmill running 24 as mechanisms to induce neuromuscular fatigue. Consistently, these types of exercise/fatigue models generally took less than 10 to 15 minutes to complete and required exercise intensities in which participants exercised to the point of failure, as defined by predetermined criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation